Dose-response association of leisure time physical activity with mortality in adults with major chronic diseases - Sun, Jiahong; Wu, Han; Zhao, Min; Magnussen, Costan G.; Xi, Bo (Frontiers in Nutrition, 2022)
We aimed to evaluate the association between leisure-time physical activity (PA) and mortality risk in adults with major chronic diseases. A total of 170,579 adults with major chronic diseases aged 30-84 years from the U.S. National Health Interview Surveys (1997-2014) with linkage to the National Death Index through December 31, 2015 were included in this study. During a median follow-up of 7.25 years, 36,914 adults with chronic diseases died from all causes, 8,767 died from cardiovascular disease (CVD), and 9,090 died from cancer. Compared with participants with no leisure-time PA, those with a low level (10-59 minutes/week) of total leisure-time PA had a 23% (hazard ratio [HR] 0.77, 95% confidence interval [CI] 0.73-0.82) reduced risk of all-cause mortality. Adults with higher levels of leisure time had more reduced risk of all-cause mortality, as well as CVD-specific and cancer-specific mortality. Adults with leisure-time PA ≥1500 minutes/week had more reduced risk of CVD-specific mortality (61%) but less reduced risk of cancer-specific mortality (29%) compared with the reduced risk of all-cause mortality (43%). There was an inversely nonlinear dose-response relationship between leisure-time PA and all-cause and cause-specific mortality. Reduced risk of all-cause and cancer-specific mortality between leisure-time light-to-moderate PA and vigorous-intensity PA time were largely comparable. Low and high levels of leisure-time PA showed substantial survival benefits compared with no leisure-time PA in adults with major chronic diseases. The light-to-moderate-intensity leisure-time PA is largely comparable with vigorous PA to provide survival benefits for all-cause and cancer-specific mortality.